STRATEGI PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) MELALUI PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) SEBAGAI UPAYA MENINGKATKAN DAYA SAING - Syaiful Syaiful (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The government is still focused mengalakan SME sector is due in addition to one of the premises pengerak economy, the sector is labor-intensive. These SMEs have proven good performance and can bartahan in mengadapi economic crisis with quite resilient, Empowering SME Empowerment of SMEs currently in the midst of globalization and high competition, making SMEs should be unable to deal with global challenges, such as improving product and service innovation, pegembangan human resources and acceleration utilizing information and communication technology, as well as the expansion of the area of ​​marketing. This needs to be done to strengthen the competitiveness of SMEs itself, through increased competence of human resources capability, Master Card channeling capital to enlarge and improve productivity of SMEs through the use of information and communication technology (ICT). Telekomunikasi Indonesia, Tbk (Telkom) through Digital Inddonesia Enterprenuer program is committed to support SME development through utilizing ICTdan e-commerce can enhance the productivity and competitiveness of SMEs in the global market.